2017
DOI: 10.1002/app.44890
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cardanol based epoxy plasticizer by click chemistry and its action on poly(vinyl chloride)

Abstract: In recent years, the using of reproducible resource and economical and efficient synthesis method has got wide concern. Herein, an environmental-friendly plasticizer originated from cardanol was synthesized by click chemistry. First, the cardanol sulfide (CS) was obtained by click chemistry reaction between the double bond of the side chain of cardanol and mercaptoethanol. The degree of the click reaction was estimated to reach 84.7% by testing the content of sulfur. Then, the epoxidation of the hydroxyl was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…They also observed no migration of the self‐plasticized PVC films against PVC/DOP system where 15.7% of DOP leached into n‐hexane. Yao et al [ 16 ] prepared cardanol based epoxy plasticizer (CEP) by click chemistry and studied its action on PVC. They observed that CEP could increase the tensile strength of PVC when used in a small amount and could increase the plasticity of PVC when used in larger quantity.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed no migration of the self‐plasticized PVC films against PVC/DOP system where 15.7% of DOP leached into n‐hexane. Yao et al [ 16 ] prepared cardanol based epoxy plasticizer (CEP) by click chemistry and studied its action on PVC. They observed that CEP could increase the tensile strength of PVC when used in a small amount and could increase the plasticity of PVC when used in larger quantity.…”
Section: Introductionmentioning
confidence: 99%
“…Peaks appeared at δ 5.41 ppm, which were associated with protons of hydroxyl groups. The signal of the olefin groups appeared at δ 5.44 ppm, and the signals of the protons for the benzene rings could be observed at δ 6.71, δ 6.82 and δ 7.18 ppm [ 19 , 21 , 22 ]. In comparison to the 1 H NMR spectrum of cardanol, a new signal appeared at δ 4.75 ppm, which was attributed to the protons of methylene groups connected to alkynyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Cardanol can be converted into a polyol or a polyamine through a straightforward reaction with 2‐mercaptoethanol or cysteine hydrochloride, respectively . The resulting polyol‐ and polyamine‐based cardanols were further used in the synthesis of PURs.…”
Section: Synthesis Of Aromatic Polymeric Materials Through Click Reacmentioning
confidence: 99%